2021
DOI: 10.3847/2041-8213/abdcb4
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Disruption Event Hosts Are Green and Centrally Concentrated: Signatures of a Post-merger System

Abstract: We study the properties of the galaxies hosting the first 19 tidal disruption events (TDEs) detected with the Zwicky Transient Facility (ZTF) within the context of a carefully constructed, representative host galaxy sample. We find that the ZTF sample of TDE hosts is dominated by compact "green valley" galaxies. After we restrict the comparison sample to galaxies with a similar concentration, as measured by the Sérsic index, we find this green valley overrepresentation is even larger. That is, concentrated red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 40 publications
7
50
0
Order By: Relevance
“…About 15% of these are spectroscopically confirmed SN. The photometric selection recovers all ZTF TDEs and all large-amplitude flares from Seyfert galaxies that have been reported in earlier work (12,23,42).…”
Section: A Flare Selection and Photometrysupporting
confidence: 66%
“…About 15% of these are spectroscopically confirmed SN. The photometric selection recovers all ZTF TDEs and all large-amplitude flares from Seyfert galaxies that have been reported in earlier work (12,23,42).…”
Section: A Flare Selection and Photometrysupporting
confidence: 66%
“…The extinction is roughly consistent with the Galactic foreground extinction of E(B − V) = 0.06 (Schlafly & Finkbeiner 2011). The estimated mass combined with the extinction-corrected rest-frame colour u − r = 1.89 ± 0.02 mag places the host galaxy near the "green valley" region (Schawinski et al 2014) of the mass colour diagram, in which the TDE host galaxies seems to be over represented compared to the general galaxy population (Law- Smith et al 2017;Hammerstein et al 2021).…”
Section: Spectral Energy Distributionsupporting
confidence: 70%
“…The overrepresentation of TDEs in poststarbursts was initially estimated to be as large as a factor ∼ 100 for E+A and ∼ 30 for quiescent Balmer strong hosts (French et al 2016;Graur et al 2018). Law-Smith et al (2017) showed that, once accounting for selection effects, the E+A poststarburst preference should be reduced by a factor ≈ 4, bringing the overall poststarburst preference to nearly 15 − 30, as later confirmed by Hammerstein et al (2021).…”
Section: Introductionmentioning
confidence: 89%
“…The opening of this golden era for TDEs has come with its own surprises. Together with the accumulation of the first dozens of detections, population studies of TDE hosts have revealed that these events are significantly overrepresented in poststarburst galaxies (Arcavi et al 2014;French et al 2016French et al , 2017Law-Smith et al 2017;Graur et al 2018;French et al 2020;Hammerstein et al 2021). The spectra of these galaxies lack strong emission lines, suggesting low current star formation rates, but feature strong Balmer absorption lines, a signature that reveals the presence of many young stars, and it is associated with a starburst over the last ≈1 Gyr (see e.g.…”
Section: Introductionmentioning
confidence: 99%